KEANEKARAGAMAN TUMBUHAN LIAR EDIBEL PADA EKOSISTEM SAWAH DI SEKITAR KAWASAN HUTAN GUNUNG SALAK BIODIVERSITY OF EDIBLE WILD PLANTS ON PADDY ECOSYSTEM OF GUNUNG SALAK FOREST AREA - Suwena , Made (Jurnal Biologi Udayana; Vol XI, No 1, 2007)
The research aimed to know edible plants diversity on paddy field ecosystem around Gunung Salak forest area was conducted at Cidahu, Cipelang Cipeuteuy, Gunung Bundar 2, Parakan Salak, Pulosari, Tamansari, and Tapos from September 2004 until August 2005. Vegetation analysis using quadratic method while usefulness of plants were based on local experts. Data analysis of diversity index was based on Shannon & Wiener, evenness index was based on Simpson’s, and similarity index was based on Sorensen. There area 73 species of edible wild plants from 37 family were found with diversity index was 3.599, evennes index was 0.834, and similarity index between location was 0.51-0.73. Ageratum conyzoides was found as the dominant plant in the surveyed area. The edible wild plants were utilized by local inhabitants as vegetable (58%), as herb (36 %), as source of carbohydrate (4%), as fruits (1%) and as spice (1 %)
Keywords: biodiversity; edible wild plants; sawah field; Gunung Salak